Saluran Pemasaran Bawang Merah (Allium ascalonicum) di Desa Ohoitel Kecamatan Pulau Dullah Utara Kota Tual - Far Far, Inda E F; Thenu, Stephen F W; Wenno, Noviar F (Universitas Pattimura, 2025)
This study uses a purposive sampling method. Certain considerations. The location was determined intentionally because in Ohoitel Village, North Dullah Island District, Tual City, the samples were 42.6% of the total number of 24 farmers used, only 10 populations. These results conclude: 1) Marketing Channels for shallot (Allium ascalonicum) in Ohoitel Village, North Dullah Island District, Tual City, have two marketing channels. Marketing pattern I: farmers - consumers, and marketing pattern II: farmers - retailers - consumers. The total margin of marketing channel I is zero because there is no price difference between farmers and consumers, and the total marketing cost is 2,026; the profit obtained is 22,974; and 2) The results of the efficiency of shallots can be seen that the value of the efficient marketing channel has an efficiency value of 100 percent. It can be seen that marketing channel 1 is efficient for channel II; there is an efficiency value of 0.16%, which means that marketing in Ohoitel Village itself can be said to be inefficient because the low quality of production by farmers results in lower selling prices or profits received by farmers.